Prednisolone dose-dependently influences inflammation and coagulation during human endotoxemia - de Kruif, Martijn D; Lemaire, Lucienne C; Giebelen, Ida A; van Zoelen, Marieke A D; Pater, Jennie M; van den Pangaart, Petra S; Groot, Angelique P; de Vos, Alex F; Elliott, Peter J; Meijers, Joost C M; Levi, Marcel; van der Poll, Tom (Journal of Immunology, 2007)
The effects of steroids on the outcome of sepsis are dose dependent. Low doses appear to be beneficial, but high doses do not improve outcome for reasons that are insufficiently understood. The effects of steroids on systemic inflammation as a function of dose have not previously been studied in humans. To determine the effects of increasing doses of prednisolone on inflammation and coagulation in humans exposed to LPS, 32 healthy males received prednisolone orally at doses of 0, 3, 10, or 30 mg (n = 8 per group) at 2 h before i.v. injection of Escherichia coli LPS (4 ng/kg). Prednisolone dose-dependently inhibited the LPS-induced release of cytokines (TNF-alpha and IL-6) and chemokines (IL-8 and MCP-1), while enhancing the release of the anti-inflammatory cytokine IL-10. Prednisolone attenuated neutrophil activation (plasma elastase levels) and endothelial cell activation (von Willebrand factor). Most remarkably, prednisolone did not inhibit LPS-induced coagulation activation, measured by plasma concentrations of thrombin-antithrombin complexes, prothrombin fragment F1+2, and soluble tissue factor. In addition, activation of the fibrinolytic pathway (tissue-type plasminogen activator and plasmin-alpha(2)-antiplasmin complexes) was dose-dependently enhanced by prednisolone. These data indicate that prednisolone dose-dependently and differentially influences the systemic activation of different host response pathways during human endotoxemia.